Expanding the toolbox for enantioselective sulfide oxidations: Streptomyces strains as biocatalysts - Mascotti, María Laura (2013)
Sulfide oxidase activity ofStreptomyces genus is reported here for the first time. Three Streptomyces strains were selected as new tools to access to enantioenriched R- and S-dialkyl sulfoxides. The bacterial screening was carried out using cyclohexyl methyl sulfide as model substrate.Both sulfoxide antipodes were obtained in a one-pot, time-dependent biotransformation employing S. phaeochromogenes NCIMB 11741 as biocatalyst. S. flavogriseus ATCC 33331produced mainly the S-enantiomer, while S. hiroshimensis ATCC 27429 yielded enantiopure R-cyclohexyl methyl sulfoxide.